2018
DOI: 10.1186/s12944-018-0898-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of serum triglyceride level on the prognosis of patients with hepatocellular carcinoma in the absence of cirrhosis

Abstract: BackgroundThe liver plays an important role in the metabolism of lipid and lipoprotein. Dyslipidemia has been demonstrated to be related with several cancers, but the association between serum lipid and hepatocellular carcinoma (HCC) in the absence of cirrhosis remains unclear.MethodsA total of 2528 patients with HCC at the Beijing Ditan Hospital between February 2008 and December 2017 were retrospectively included in the study. We identified 200 patients with HCC without cirrhosis by histopathology, imaging, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Consequently, there is also a discrepancy in literature reports, depending on HCC-comorbidities and associated risk factors. Increased levels of serum triglycerides were reported in HCC patients without cirrhosis [ 51 ], and another report found decreased levels of triglycerides and cholesterol to be associated with progression in hepatic pathological conditions [ 52 ]. Our finding of downregulation of lipid species in HCC patients in both blood and liver might be explained by disruption of lipid homeostasis that balance lipoprotein synthesis along with consumption of lipids by the rapidly proliferating HCC tumor cells [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there is also a discrepancy in literature reports, depending on HCC-comorbidities and associated risk factors. Increased levels of serum triglycerides were reported in HCC patients without cirrhosis [ 51 ], and another report found decreased levels of triglycerides and cholesterol to be associated with progression in hepatic pathological conditions [ 52 ]. Our finding of downregulation of lipid species in HCC patients in both blood and liver might be explained by disruption of lipid homeostasis that balance lipoprotein synthesis along with consumption of lipids by the rapidly proliferating HCC tumor cells [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“… 147 , 257 Furthermore, diminished levels of circulating TG in patients with HCC are associated with worse overall survival. 258 However, due to the unspecific nature of these changes, they remain a generic biomarker of liver dysfunction. On the other hand, the changes in specific TG species may be more useful.…”
Section: Diagnostic Potential Of Circulating Lipidsmentioning
confidence: 99%
“…However, the association between TG and the survival of tumor patients is contradictory. Some studies observed that high level TG can improve the survival of cancer patients [32][33] . On the contrary, other studies [30][31][32][33][34] has shown that high TG can lead to poor prognosis in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies observed that high level TG can improve the survival of cancer patients [32][33] . On the contrary, other studies [30][31][32][33][34] has shown that high TG can lead to poor prognosis in cancer patients. In our study, TG≥1.7 mmol/L(HR 0.77, 95%CI 0.69-0.86) were protective factor of survival.…”
Section: Discussionmentioning
confidence: 99%